2009
DOI: 10.1007/s10681-009-9997-1
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of bread wheat quality: joint use of the phenotypic information brought by technological tests and the genetic information brought by HMW and LMW glutenin subunits

Abstract: Attempts have been made to predict Chopin alveograph or French bread-making tests, using tree-based models and PLS regressions. Data came from three sets of trials, involving 130, 214 and 103 different genotypes, which were described for HMW-GS, LMW-GS and small-scale tests currently used in breeding programs. Segmentation trees and PLS regressions indicated that HMW-GS and LMW-GS were not sufficient to explain alone the variability of bread wheat quality. This could be partly due to “allele × environment” and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 39 publications
3
22
0
1
Order By: Relevance
“…Liang et al (2010) did not observe significant differences in the SDS-SV, SI, development time of dough, and gluten strength between alleles 1 and 2*, which suggests that they have a positive effect on the strength and rheological properties of the dough. Oury et al (2009) have also reported that alleles 1 and 2* are better qualified for bread-making than the null subunit.…”
Section: Analysis Of Principal Componentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Liang et al (2010) did not observe significant differences in the SDS-SV, SI, development time of dough, and gluten strength between alleles 1 and 2*, which suggests that they have a positive effect on the strength and rheological properties of the dough. Oury et al (2009) have also reported that alleles 1 and 2* are better qualified for bread-making than the null subunit.…”
Section: Analysis Of Principal Componentsmentioning
confidence: 97%
“…Studies have shown that the HMW-GS have the highest influence on the rheological properties of dough and breadmaking quality (PEÑA et al, 2005;OURY et al, 2009;LI et al, 2010;ZHENG et al, 2011;HERNÁNDEZ et al, 2012). The alleles 1 and 2* of Glu-A1 have been found to have a better effect on bread-making quality when compared to a null allele (GUPTA et al, 1994;HE et al, 2005).…”
Section: Sds-page Analysismentioning
confidence: 99%
“…Alleles encoded at the Glu-A1 had no effect on color, dough rheological characteristics, and bread quality (Table 5). Oury et al (2010) also reported that 1 and 2* subunits had no significant effects on alveograph parameters and baking properties. However, these subunits were associated with a higher loaf volume compared to the Null subunit (Peña et al 2005;Vázquez et al 2012).…”
Section: Baking Qualitymentioning
confidence: 98%
“…By screening an ethyl methanesulfonate-induced mutant population, knockout mutants were identified for all five subunits and missense mutants for Ax1, Dx2, and Dy12 ( Figure 1A and Supplemental Table 1). Because Ax1 and Bx14 are frequently used in international wheat quality breeding programs (Oury et al, 2010;Rasheed et al, 2014), we comparatively analyzed two knockout mutants of Ax1 (ma1-1 and ma1-2), two knockout mutants of Bx14 (mb14-1 and mb14-2), one double mutant (ma1-1mb14-1) lacking both Ax1 and Bx14, and one missense mutant of Ax1 (ma1-3) to reveal the contributions of the two subunits to dough functionality and bread quality. For ma1-3, the single amino acid substitution (G330E) in Ax1 was confirmed to be the cause of the reduced electrophoretic mobility of the mutant Ax1 protein by bacterial expression (Supplemental Figure 1).…”
mentioning
confidence: 99%